2016
DOI: 10.1002/2016wr019110
|View full text |Cite
|
Sign up to set email alerts
|

Observed and simulated hydrologic response for a first‐order catchment during extreme rainfall 3 years after wildfire disturbance

Abstract: Hydrologic response to extreme rainfall in disturbed landscapes is poorly understood because of the paucity of measurements. A unique opportunity presented itself when extreme rainfall in September 2013 fell on a headwater catchment (i.e., <1 ha) in Colorado, USA that had previously been burned by a wildfire in 2010. We compared measurements of soil‐hydraulic properties, soil saturation from subsurface sensors, and estimated peak runoff during the extreme rainfall with numerical simulations of runoff generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 137 publications
1
49
0
Order By: Relevance
“…However, in areas with patchy burn severity, an approach that considers infiltration variability may be preferable (e.g., Ebel et al. , ; McGuire et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in areas with patchy burn severity, an approach that considers infiltration variability may be preferable (e.g., Ebel et al. , ; McGuire et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have arrived at mixed conclusions regarding the importance of correlation length on run‐off response. Corradini et al () found that variations in correlation length had only a minimal effect on simulated run‐off hydrographs, whereas field‐based investigations and other modeling studies suggest that soil patches with low‐infiltration rates can substantially alter the run‐off response (Ebel et al, (); Sheridan et al, ()). The use of Ke* could provide an efficient framework for determining the portion of the parameter space where correlation length plays an important role in the basin‐scale run‐off response.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to condense information about a spatially variable K s field into a single value of K e that characterizes the run-off response at the basin scale would be valuable for rapid integration of field measurements into simplified hydrologic models and for debris flow hazard assessment purposes. Relationships between K e and K s also help to bridge the gap between hydrologic studies conducted at different scales, such as those that effectively constrain K e through postevent model calibration at the basin scale (e.g., Langhans et al, (2016); Rengers, McGuire, Kean, Staley, & Hobley, (2016)) and those that quantify K s through small-scale field measurements (e.g., Ebel, Rengers, & Tucker, (2016); Langhans et al, (2016)).…”
mentioning
confidence: 99%
“…Few efforts have measured or estimated K fs recovery for more than 3 years after wildfire, belying the importance of K fs for numerical modelling of hydrologic recovery and associated water-related hazards at the plot-scale (e.g., Ebel, 2013) and watershed scale (Cydzik & Hogue, 2009;Ebel, Rengers, & Tucker, 2016;Rengers, McGuire, Kean, Staley, & Hobley, 2016). Here, we have reviewed the literature and isolated the studies that investigated the recovery of K fs for more than 3 years following wildfire, which are summarized in Table 2.…”
Section: Although the Factors Shown Inmentioning
confidence: 99%